The many mothers of Dolores Moore - Fajardo, Anika (Gallery Books, 2025)
For fans of Rebecca Serle and Elizabeth Acevedo, a magically insightful novel about a woman's journey to discover her roots and what it means to carry our ancestors with us. In the span of a year, Dolores Moore has become a thirty-five-year-old orphan. After the funeral of the last living member of her family, Dorrie has never felt more lost and alone. That is, except for a Greek chorus of deceased relatives whose voices follow her around giving unsolicited advice and opinions. And they're only amplifying Dorrie's doubts about keeping the deathbed promise she made to return to her birthplace in Colombia. Fresh off a breakup with her long-term boyfriend, laid off from her job as a cartographer, and facing a daunting inheritance of her mothers' aging Minneapolis Victorian and two orange tabbies, how can she possibly leave the country now? But when an old flame offers to housesit, the chorus agrees that there's no room for excuses. Armed with only a scrap of a handdrawn map, Dorrie sets off to find out where--and who--she came from.